Impact on knowledge and behaviour of the general population of two different methods of solid waste management: An explorative cross-sectional study. Issue 6 (June 2014) - Del Cimmuto, Angela; Mannocci, Alice; Ribatti, Domenico; Boccia, Antonio; La Torre, Giuseppe
The objectives of the present study were to evaluate knowledge among general population about the risks factors of waste management, to estimate the feeling of anxiety concerning the waste, and to compare knowledge of two different methods for collecting municipal solid waste (MSW): a street separate collection system and a door-to-door separate collection system. A cross-sectional study was performed, administering an anonymous questionnaire to 180 inhabitants in Aprilia, Latium, Italy. The study sample consisted of 183 citizens: 64 in the intervention group and 119 in the control group. The intervention was represented by a campaign of door-to-door collection. The correct implementation of separate collection of waste was 87.5% in the intervention group and 63% in the control group ( p <0.001). For both groups, the favourite type of waste collection was door-to-door ( p =0.013); a high difference concerning the quality of information was found ( p <0.0001): in the intervention group, 84% declared to be satisfied (67% sufficient and 17.2% good), while in the control group, 21% declared to be satisfied (16.8% sufficient and 4.2% good). The advice mainly reported from the control group respondents was to increase the size of the information pack (80.7%, p =0.024). The information campaign seemed to increase people's awareness about the problem, improving the management of waste and household waste. The door-to-door collection was appreciated and preferred by both groups. The adoption of a door-to-door scheme seems to be a winning option mostly because it is supported by an information and education system for the citizens.